Alumina-silicon dioxide aerogel and its preparation method and application

By using a common precursor and a weak alkali environment to induce the secondary condensation of silicone hydroxyl groups in the normal pressure drying process of alumina-silica aerogels, the existing technology solves the cumbersome process, low aluminum content, and difficulty in hydrophobic modification. and other problems, the preparation of aerogels with high aluminum-to-silicon ratio, low density, and high temperature resistance has been achieved, improving its performance in various application fields.

CN118908255BActive Publication Date: 2025-01-21ANHUI ZHONGKE HENGAN SAFETY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411398534.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-21
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art has problems such as cumbersome process, low aluminum content, difficulty in hydrophobic modification, and high product density when preparing alumina-silica aerogels, which limits its application in high-temperature heat insulation, thermal insulation coatings and other fields.

Method used

In the process of preparing alumina-silica aerogels by drying under normal pressure, a common precursor is used to introduce aluminum sources and silicon sources, and a weak alkaline environment is constructed during the aging stage to induce secondary condensation of silicon hydroxyl groups to form silica The "shell" layer improves the gel's temperature resistance and hydrophobic modification capabilities.

Benefits of technology

A high aluminum-to-silicon ratio, low density, and high-temperature-resistant yttium oxide-silica aerogel has been achieved, improving its application performance in high-temperature insulation, thermal insulation coatings, catalyst carriers, or adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908255B_ABST
    Figure CN118908255B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of aerogel preparation, and in particular to an alumina-silica aerogel and a preparation method and application thereof. The preparation method provided by the present invention induces secondary condensation of silanol groups by constructing an alkaline environment during the aging stage, and the obtained alumina-silica aerogel product has a lower density. For example, the tap density of the sample corresponding to the Al / Si molar ratio of 0.60 is as low as 0.091 g / cm 3 After being treated at 1000℃ for 2 h, the tap density is still as low as 0.243 g / cm 3 , which is comparable to that of supercritical dried samples. At the same time, this preparation method can increase the Al / Si molar ratio from the commonly reported 0.1 to 1.0, and the increase in the aluminum-silicon molar ratio has a significant improvement on the temperature resistance of the aerogel. For example, the specific surface area of ​​the sample with an Al / Si molar ratio of 0.60 after treatment at 1000℃ / 2 h is still as high as 475.24 m 2 / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel preparation, in particular to an alumina-silicon dioxide aerogel and a preparation method and application thereof. Background Art

[0002] Alumina-silica aerogel is a lightweight solid material with a three-dimensional network nanoporous structure and nanoparticles as the skeleton. It can still maintain a high specific surface area (80~103 m2) after heat treatment at 1100~1300℃. 2 / g), is one of the aerogel materials with outstanding thermal insulation and temperature resistance in aerobic environment at present.

[0003] At present, the mature preparation methods of alumina-silica aerogel mostly adopt organic or inorganic aluminum salt and organosilicon alkoxide as raw materials, and are prepared by sol-gel method combined with supercritical drying method. At present, this method also has some applications in the preparation of alumina-silica aerogel. For example, patent CN109621849A uses cheap inorganic aluminum salt to prepare alumina wet gel by sol-gel. Since the aluminum gel skeleton cannot be directly alkylated, it is then impregnated with TEOS hydrolyzate to coat a layer of silica on the skeleton of the wet gel, and then hydrophobic modification and atmospheric pressure drying are performed to obtain silica-coated alumina composite aerogel; patent CN111215007A introduces a silicon source containing hydrophobic groups by a co-precursor method, and then uses ammonia water for gelation, and obtains alumina-silica aerogel with certain elasticity after solvent replacement and drying. However, the process control conditions of this method are extremely strict, the required equipment is expensive, and it has certain dangers, which is not conducive to large-scale and continuous production.

[0004] In addition, silicon sources such as methyl orthosilicate or ethyl orthosilicate can be directly composited with inorganic aluminum salts for gelation without coating with a silicon layer, and the products can be obtained by solvent replacement and atmospheric pressure drying. In comparison, atmospheric pressure drying equipment is safe and easy to operate, has low cost, and has fewer restrictions on sample shape and size. However, the highest Al / Si molar ratio reported in the literature is only 0.1 (Ji X, Zhou Q, Qiu G, et al. Preparation of monolithic silica-based aerogels with high thermal stability by ambient pressure drying [J]. Ceramics International, 2018, 44 (11): 11923-11931.).

[0005] In summary, there are still some problems in the preparation of alumina-silica aerogel by atmospheric pressure drying: First, the silicon protective layer is introduced by constructing a "core-shell" structure, and the process is cumbersome and complicated, and the amount of silicon doping is very limited. The number of available alkyl group grafting sites in the subsequent hydrophobic modification stage is reduced, resulting in large shrinkage of the product during the drying process and high density. Second, the use of ammonia water as a gelling agent makes the solution system very sensitive to aluminum ions. As the aluminum content increases, flocculation and phase separation will immediately occur, making it difficult to increase the Al / Si molar ratio; third, the introduction of a large amount of silicon source containing hydrophobic groups through a co-precursor will affect the temperature resistance of the product. Therefore, it is an urgent problem to develop a simple, low-cost atmospheric pressure preparation process to obtain alumina-silica aerogel products with a high aluminum-silicon ratio, low density, and high temperature resistance. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide an alumina-silica aerogel and a preparation method and application thereof. The preparation method provided by the present invention can prepare an alumina-silica aerogel with a high aluminum-silicon ratio by drying at normal pressure, and the aerogel has good high temperature resistance, low density and high specific surface area.

[0007] The present invention provides a method for preparing an alumina-silicon dioxide aerogel, comprising the following steps:

[0008] S1) converting alumina sol and silica sol into alumina-silica gel under the action of additives including a coagulant;

[0009] S2) heating the alumina-silica gel obtained in step S1) in a weak alkaline source for solvent replacement; the pH of the weak alkaline source is 7.0-11.0;

[0010] S3) The alumina-silica gel after the solvent replacement in step S2) is subjected to surface alkylation treatment under the action of a hydrophobic modifier, and then dried at normal pressure to obtain an alumina-silica aerogel.

[0011] The present invention first converts alumina sol and silica sol into alumina-silica gel under the action of an additive including a coagulant. Specifically, the present invention mixes and stirs alumina sol and silica sol to obtain alumina-silica sol, and the mixing and stirring time is 2 h to 12 h, preferably 5 h to 7 h, and more preferably 6 h; then the alumina-silica sol and the coagulant are mixed, and left to stand for natural aging for 12 h to 24 h, preferably 23 h to 24 h, and preferably left to stand for natural aging for 24 h to obtain alumina-silica gel. The coagulant of the present invention is selected from one or more of propylene oxide or epichlorohydrin. The molar ratio of the aluminum element in the alumina sol of the present invention to the silicon element in the silica sol is less than 1.0; the molar ratio of the amount of the coagulant added to the aluminum element in the alumina sol is 5 to 20.

[0012] The additive of the present invention may further include a drying control agent, which is selected from one of formamide and N,N-dimethylformamide. In some embodiments of the present invention, the alumina sol and the silica sol are converted into alumina-silica gel under the action of an additive including a coagulant and a drying control agent, and the ratio of the molar amount of the drying control agent to the total molar amount of aluminum and silicon elements in the alumina sol and the silica sol is less than 1.0.

[0013] The alumina sol of the present invention is obtained from an aluminum source, an alcohol solvent and water, specifically, the aluminum source, the alcohol solvent and water are mixed for hydrolysis reaction, and the alumina sol is obtained after cooling. The aluminum source of the present invention is an inorganic aluminum source, specifically selected from one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, aluminum isopropoxide or aluminum sec-butoxide; the alcohol solvent is selected from one or more of methanol, anhydrous ethanol, isopropanol and n-butanol. The molar ratio of the aluminum source, the alcohol solvent and water of the present invention is 1: (4~15): (8~20). The temperature of the hydrolysis reaction of the present invention is 30℃~80℃, and the time of the hydrolysis reaction is 30 min~100 min, preferably 60 min~80 min, and more preferably 70 min.

[0014] The silica sol of the present invention is obtained by a silicon source, an alcohol solvent and water under the action of an acidic catalyst; specifically, the silicon source, the alcohol solvent, water and the acidic catalyst are mixed and stirred to obtain the silica sol. The silicon source of the present invention is selected from one or more of methyl orthosilicate, ethyl orthosilicate, silica sol or water glass; the alcohol solvent is selected from one or more of methanol, anhydrous ethanol, isopropanol and n-butanol. The molar ratio of the silicon source, the alcohol solvent and water of the present invention is 1: (2~12): (1~10). The mixing and stirring time of the present invention is 10 min~240 min. The pH of the silica sol obtained by the present invention is 2~3. The pH of the silica sol obtained by the present invention is adjusted by the acidic catalyst, and the acidic catalyst is selected from one of hydrochloric acid, nitric acid, acetic acid, etc. In some embodiments of the present invention, the concentration of the acidic catalyst is 0.1 mol / L~10 mol / L.

[0015] After the alumina-silica gel obtained by the present invention is subjected to heating solvent replacement in a weak alkaline source; specifically, the obtained alumina-silica gel is immersed in a weak alkaline source for heating solvent replacement, and at a certain temperature, hydroxyl condensation can be further induced to obtain secondary cross-linked and reinforced alumina-silica gel; the pH of the weak alkaline source is 7.0~11.0. The weak alkaline source of the present invention is selected from one or more of urea, sodium carbonate, sodium acetate, sodium phosphate, sodium bicarbonate or ammonium bicarbonate. The temperature of the heating solvent replacement of the present invention is 40°C~120°C; the time of the heating solvent replacement is 8 h~48 h, preferably 45 h~48 h.

[0016] The present invention heats the obtained alumina-silica gel in a weak alkaline source for solvent replacement, and then performs surface alkylation treatment on the alumina-silica gel after the heating solvent replacement under the action of a hydrophobic modifier, and then performs normal pressure drying to obtain an alumina-silica aerogel. Specifically, the alumina-silica gel after the heating solvent replacement is immersed in a hydrophobic modifier for surface alkylation treatment, and then the gel after the alkylation treatment is dried at normal pressure to obtain an alumina-silica aerogel. The surface alkylation treatment of the present invention is a heating and standing treatment, and the temperature of the surface alkylation treatment is 40°C~80°C, preferably 50°C~70°C, and the time of the surface alkylation treatment is 4h~24h, preferably 10h~14h. The normal pressure drying of the present invention is specifically: drying at 60°C~80°C for 8h~12h, and then drying at 100°C~180°C for 6h~12h.

[0017] The hydrophobic modifier of the present invention is one of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, hexamethyldisilazane, etc. In certain embodiments of the present invention, the hydrophobic modifier is used after being mixed with an organic solvent, and the organic solvent is selected from at least one of n-hexane, n-heptane, and n-octane.

[0018] In some embodiments of the present invention, before the surface alkylation treatment, the present invention further comprises placing the alumina-silica gel after the heated solvent replacement in an organic solvent for replacement for 8 to 24 hours, preferably for replacement for 20 hours to 24 hours, and the organic solvent is selected from at least one of n-hexane, n-heptane, and n-octane. In other embodiments of the present invention, after the surface alkylation treatment, the present invention further comprises placing the alumina-silica gel after the surface alkylation treatment in an organic solvent for replacement to remove the residual hydrophobic modifier, and the organic solvent is the same as above and will not be repeated.

[0019] The preparation method provided by the present invention aims at the problem that in the prior art, after alumina sol and silica sol are converted into alumina-silica gel by a coagulant, when the aluminum content is high, subsequent surface alkylation treatment cannot be successfully carried out, that is, hydrophobic modification. The alumina-silica gel formed by the co-precursor through sol-gel is creatively subjected to solvent replacement in a weak alkaline source, and the weak alkaline source is decomposed by heating in the aging stage to create an alkaline environment to induce secondary polymerization of unreacted silanol groups, which on the one hand strengthens the gel skeleton, and on the other hand, unreacted monosilicic acid and disilicate in the system polymerize on the surface of the gel particles to form a silica "shell" layer, thereby being able to resist strong acid or strong alkaline environment erosion in the subsequent alkylation treatment process, ensuring the subsequent successful hydrophobic modification, and solving the difficult problems of complicated process, low aluminum content, difficult hydrophobic modification, high product density, etc. in the traditional process of preparing alumina-silica aerogel by normal pressure drying, and has great significance for promoting low-cost, continuous and safe production of alumina-silica aerogel.

[0020] The present invention also provides an alumina-silica aerogel obtained by the preparation method described in any of the above technical solutions. The alumina-silica aerogel obtained by the preparation method described in the present invention has high aluminum-silicon ratio, low density, high specific surface area and high temperature resistance. The present invention also provides the use of the alumina-silica aerogel obtained by the preparation method described in any of the above technical solutions in the fields of high-temperature thermal insulation, thermal insulation coatings, catalyst carriers or adsorption.

[0021] The present invention provides an alumina-silica aerogel and a preparation method and application thereof. Compared with the existing technology for preparing alumina-silica aerogel materials by drying at normal pressure, the preparation method provided by the present invention has the following advantages:

[0022] 1. The preparation method of the present invention is simple and easy to operate, has low requirements on equipment, and has good repeatability. In the preparation method, aluminum source and silicon source are simultaneously introduced through a co-precursor, and an alkaline environment is introduced during the aging stage after gelation to induce silanol condensation, and the surface alkylation treatment can be directly performed, thereby avoiding the cumbersome process problems existing in the prior art such as secondary impregnation to introduce a silicon protective layer and then repeatedly replace and remove the residual silicon source, and the cost is low and the process stability is high.

[0023] 2. The alumina-silica aerogel prepared by the present invention has the advantages of high aluminum-silicon molar ratio, low density, and strong temperature resistance. Compared with the prior art, by constructing an alkaline environment during the aging stage to induce secondary condensation of silanol groups, on the one hand, the gel skeleton is strengthened, and on the other hand, the unreacted monosilicic acid and disilicate in the system polymerize on the surface of the gel particles to form a silica "shell" layer, thereby being able to resist erosion by strong acid or strong alkali environments during subsequent alkylation treatments. Therefore, the product obtained by this preparation method has a lower density. For example, the tap density of the sample corresponding to an Al / Si molar ratio of 0.60 is as low as 0.091 g / cm 3 After being treated at 1000℃ for 2 h, the tap density is still as low as 0.243 g / cm 3 , which is comparable to that of supercritical dried samples. At the same time, this preparation method can increase the Al / Si molar ratio from the commonly reported 0.1 to 1.0, and the increase in the aluminum-silicon molar ratio has a significant improvement on the temperature resistance of the aerogel. For example, the specific surface area of ​​the sample with an Al / Si molar ratio of 0.60 after treatment at 1000℃ / 2 h is still as high as 475.24 m 2 / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of the process for preparing the alumina-silicon dioxide aerogel of the present invention;

[0025] Figure 2 A schematic diagram of the reaction mechanism of the preparation method of the present invention for constructing a weak base environment in the aging stage to induce secondary condensation of silanol groups;

[0026] Figure 3 This is a diagram showing the change in tap density of the alumina-silicon oxide aerogel prepared in Example 1 after heat treatment at different temperatures;

[0027] Figure 4 This is a graph showing the change in specific surface area of ​​the alumina-silicon oxide aerogel prepared in Example 1 after heat treatment at different temperatures;

[0028] Figure 5 The scanning electron microscope images of the alumina-silicon oxide aerogel prepared in Example 1 before and after heat treatment at 1000°C / 2 h;

[0029] Figure 6 XRD diagram of the crystalline phase structure change of the alumina-silicon oxide aerogel prepared in Example 1 before and after heat treatment at 1000°C / 2 h;

[0030] Figure 7 This is a graph showing the change in room temperature thermal conductivity of the alumina-silicon oxide aerogel prepared in Example 1 after heat treatment at different temperatures;

[0031] Figure 8 These are optical photographs of the corresponding samples of Examples 1 to 5 and Comparative Examples 2 to 6 before and after hydrophobic modification. DETAILED DESCRIPTION

[0032] The present invention discloses an alumina-silica aerogel and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0033] The present invention provides a method for preparing a high aluminum-silicon ratio, low density, high temperature resistant aluminum oxide-silicon dioxide aerogel by drying at normal pressure, such as Figure 1 As shown, Figure 1 The schematic diagram of the process for preparing the alumina-silicon dioxide aerogel of the present invention is as follows: Figure 1 It can be seen that the preparation method of alumina-silica aerogel of the present invention comprises the following steps: 1) hydrolyzing an aluminum source under certain conditions to obtain an alumina sol; 2) hydrolyzing a silicon source under certain conditions to obtain a silica sol; 3) mixing alumina and silica sol according to a required ratio, adding an appropriate amount of desiccant, and stirring evenly at room temperature; 4) adding an appropriate amount of accelerator propylene oxide to the mixed sol, stirring evenly, and then standing to obtain an alumina-silica gel; 5) immersing the wet gel in a weak alkaline solution at a certain temperature to induce hydroxyl condensation to obtain a secondary cross-linked reinforced alumina-silica gel; 6) performing surface alkylation treatment on the gel after the secondary reinforcement, and finally drying at normal pressure to prepare alumina-silica aerogel with a high aluminum-silicon ratio, low density, and high temperature resistance.

[0034] The present invention will be further described below in conjunction with embodiments:

[0035] Example 1

[0036] (1) Preparation of alumina sol

[0037] Aluminum chloride hexahydrate was added to a mixed solvent of anhydrous ethanol and deionized water at a molar ratio of aluminum chloride hexahydrate: anhydrous ethanol: deionized water = 1:10:14, stirred in a water bath at 50°C for 70 min, and cooled to room temperature to obtain an alumina sol.

[0038] (2) Preparation of silica sol

[0039] According to the molar ratio of ethyl orthosilicate: anhydrous ethanol: deionized water = 1:5:2, ethyl orthosilicate was added to anhydrous ethanol, and after stirring for 10 min, deionized water was slowly added and stirred for 30 min. Then, 0.1 mol / L hydrochloric acid was added to adjust the pH of the mixed solution to between 2 and 3, and a uniform and transparent silica sol was obtained.

[0040] (3) Preparation of alumina-silica sol

[0041] According to the molar ratio of aluminum:silicon = 0.6, 57.54 g of the aluminum sol in (1) and 51.47 g of the silica sol in (2) were taken and mixed and stirred, and then 15.20 g of N,N-dimethylformamide was added as a drying control agent, and stirred at room temperature for 6 hours to obtain an alumina-silica sol.

[0042] (4) Preparation of alumina-silica gel

[0043] According to the molar ratio of propylene oxide: aluminum = 12:1, 41.80 g of propylene oxide was quickly added to (3). After rapid stirring for 3 minutes, the mixed solution was transferred to a tetrafluoroethylene mold. After about 10 minutes, alumina-silica gel was formed. It was left to stand at room temperature for 24 hours for natural aging.

[0044] (5) Alkaline system induces secondary condensation of silanol groups

[0045] The gel formed in (4) was immersed in a 10 wt% urea aqueous solution and then placed in a 60°C oven for solvent replacement for a total of 48 h, with the solution replaced every 12 h. During this process, on the one hand, the ethanol and solvent water in the gel network were exchanged; on the other hand, the weak alkaline environment formed by the high-temperature decomposition of urea could first induce the secondary condensation of the silanol groups in the gel skeleton to form a more complete Al-O-Si network, thereby strengthening the gel strength. In addition, the free monosilicic acid or disilicate in the gel network reacted with the silanol groups on the surface of the gel skeleton to form a silicon "shell", which could resist strong acid or strong base erosion during the subsequent alkylation treatment. The specific reaction mechanism is as follows Figure 2 As shown, Figure 2 The schematic diagram is a reaction mechanism diagram of constructing a weak alkaline environment to induce secondary condensation of silanol groups during the aging stage of the preparation method of the present invention.

[0046] (6) Surface alkylation treatment

[0047] The gel obtained in (5) was first replaced with n-hexane for 24 h, then immersed in a 20% by volume trimethylchlorosilane (TMCS) / n-hexane solution, left at 60 °C for 12 h, and then replaced with n-hexane to remove the residual silane modifier.

[0048] (7) Drying

[0049] The gel after alkylation treatment in (6) was placed in an oven at 60°C for 8 hours, and then the oven temperature was adjusted to 120°C. After 8 hours, the gel was taken out to obtain alumina-silica aerogel.

[0050] like Figure 3 As shown, Figure 3 The tap density change diagram of the alumina-silicon oxide aerogel prepared in Example 1 after heat treatment at different temperatures is shown in FIG. Figure 3 It can be seen that the tap density of the samples heat treated for two hours below 800℃ is 0.1 g / cm 3 Below, after heat treatment at 1000℃ / 2h, the density is 0.243 g / cm 3 .

[0051] like Figure 4 As shown, Figure 4 The specific surface area of ​​the alumina-silicon oxide aerogel prepared in Example 1 after heat treatment at different temperatures is shown in FIG. Figure 4 It can be seen that the specific surface area of ​​the sample after heat treatment below 800°C did not decrease but increased slightly, which was mainly due to the thermal decomposition of organic residues and alkyl groups. After heat treatment at 1000°C / 2 h, the specific surface area of ​​the sample was still as high as 475.24 m 2 / g.

[0052] like Figure 5 As shown, Figure 5 The scanning electron microscope images of the alumina-silicon oxide aerogel prepared in Example 1 before and after heat treatment at 1000°C / 2 h are shown in FIG. Figure 5 It can be seen that the pore structure remains relatively intact after high temperature treatment, and the skeleton does not show obvious coarsening or collapse.

[0053] like Figure 6 As shown, Figure 6 The XRD diagram of the crystalline phase structure change of the alumina-silicon oxide aerogel prepared in Example 1 before and after the 1000°C / 2 h heat treatment is shown in FIG. Figure 6 It can be seen that the material is amorphous before and after heat treatment, showing excellent thermal stability.

[0054] like Figure 7 As shown, Figure 7 The room temperature thermal conductivity of the alumina-silicon oxide aerogel prepared in Example 1 after heat treatment at different temperatures is shown in FIG. Figure 7 It can be seen that the room temperature thermal conductivity of the sample heat treated at 800°C for two hours basically remains at around 0.025 W / m·K. After heat treatment at 1000°C / 2 h, the room temperature thermal conductivity of the sample increases to 0.033 W / m·K.

[0055] Embodiment 2~5

[0056] Examples 2 to 5 are similar to Example 1 in preparing a high aluminum-silicon ratio, high temperature resistant alumina-silica aerogel by atmospheric pressure drying. The difference from Example 1 is that the ratio of alumina to silica sol in step (3) of Examples 2 to 5, that is, the elemental molar ratio of aluminum to silicon, is 0.25, 0.20, 0.15 and 0.10, respectively. The addition amount of the drying control agent (N,N-dimethylformamide) in step (3) of Examples 2 to 5 and the coagulant (propylene oxide) in step (4) are also changed successively. The specific reactant ratio is shown in Table 1 (the data of Example 1 is also recorded in Table 1). The other processes are the same as Example 1.

[0057] Table 1

[0058]

[0059] It can be seen from the table that with the increase of Al / Si molar ratio, the tap density of different samples after treatment at 1000℃ / 2h shows a decreasing trend, indicating that a higher Al / Si molar ratio can resist sintering shrinkage, help improve the temperature resistance of the sample, and maintain good structural stability, so that the specific surface area residual rate is higher after high-temperature treatment, which means lower thermal conductivity.

[0060] Comparative Example 1

[0061] According to the molar ratio of ethyl orthosilicate: anhydrous ethanol: deionized water = 1:5:2, ethyl orthosilicate is added to anhydrous ethanol, stirred for 10 min, then deionized water is slowly added and stirred for 30 min, and then 0.1 mol / L hydrochloric acid is added to adjust the pH of the mixed solution to between 2 and 3, and a uniform and transparent silica sol can be obtained. Subsequently, 51.47 g of the above sol is taken, and 0.5 mol / L ammonia solution is slowly added until the solution pH is about 7.5, and the gel is allowed to stand after stirring for three minutes. After natural aging at room temperature for 24 hours, the gel is immersed in ethanol and placed in a 60°C oven for solvent replacement for a total of 48 hours, and the solution is replaced every 12 hours. The subsequent hydrophobic modification and drying process is the same as in Example 1, and finally a pure silica aerogel is obtained.

[0062] The tap density of the silica aerogel prepared in Comparative Example 1 is 0.135 g / cm 3 After heat treatment at 1000℃ / 2h, the density is 0.653 g / cm 3 The specific surface area of ​​the silica aerogel prepared in Comparative Example 1 is 754.33 m 2 / g, and the specific surface area after heat treatment at 1000℃ / 2h is 43.75 m 2 / g; the thermal conductivity of the silica aerogel prepared in Comparative Example 1 is 0.023 W / m·K at room temperature, and the thermal conductivity increases to 0.241 W / m·K after heat treatment at 1000℃ / 2 h. Comparing the data of the embodiments given in Table 1, it can be seen that the alumina-silica aerogel prepared in the present invention has outstanding advantages such as low density and high temperature resistance.

[0063] Comparative Examples 2 to 6

[0064] Comparative Examples 2 to 6 are compared with Examples 1 to 5, respectively, except that the "urea aqueous solution with a mass fraction of 10 wt %" in step (5) is replaced with "anhydrous ethanol", and the other processes are the same as Examples 1 to 5.

[0065] In order to more intuitively reflect the technical advantages of the present invention, Figure 8 As shown, Figure 8 The optical photographs of the corresponding samples before and after the hydrophobic modification of Examples 1 to 5 and Comparative Examples 2 to 6 are shown in FIG. Figure 8 It can be seen that in Comparative Examples 2 to 6, only the samples corresponding to Al / Si=0.1 (molar ratio) can retain the gel skeleton after hydrophobic modification. In contrast, in Examples 1 to 5 of the present invention, when Al / Si=0.3 (molar ratio), the gel skeleton remains intact after hydrophobic modification. Therefore, the present invention provides a method for preparing alumina-silica aerogel with a high aluminum-silicon ratio at normal pressure.

[0066] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an alumina-silicon dioxide aerogel, characterized in that: The following steps are involved: S1) converting alumina sol and silica sol into alumina-silica gel under the action of an additive including a coagulant; the coagulant is one or more of propylene oxide or epichlorohydrin; the molar ratio of aluminum element in the alumina sol to silicon element in the silica sol is 0.2-1.0; S2) heating the alumina-silica gel obtained in step S1) in a weak base source for solvent replacement; the pH of the weak base source is 7.0-11.0; the weak base source is selected from one or more of urea, sodium carbonate, sodium acetate, sodium phosphate, sodium bicarbonate or ammonium bicarbonate; S3) The alumina-silica gel after the solvent replacement in step S2) is subjected to surface alkylation treatment under the action of a hydrophobic modifier, and then dried at normal pressure to obtain an alumina-silica aerogel.

2. The preparation method according to claim 1, characterized in that: In step S1), the additive further comprises a drying control agent, and the ratio of the molar amount of the drying control agent to the total molar amount of aluminum and silicon elements in the alumina sol and the silica sol is 0.1 or less; The molar ratio of the added amount of the coagulant to the aluminum element in the alumina sol is 5-20.

3. The preparation method according to claim 1, characterized in that: In step S2), the temperature of the heating solvent replacement is 40°C to 120°C; and the time of the heating solvent replacement is 8 h to 48 h.

4. The preparation method according to claim 1, characterized in that: In step S3), the temperature of the surface alkylation treatment is 40° C. to 80° C., and the time of the surface alkylation treatment is 4 h to 24 h.

5. The preparation method according to claim 1, characterized in that: In step S3), the normal pressure drying is specifically: drying at 60°C-80°C for 8 h-12 h, and then drying at 100°C-180°C for 6 h-12 h.

6. The preparation method according to claim 1, characterized in that: In step S1), the alumina sol is obtained from an aluminum source, ethanol and water in a molar ratio of 1:(4-15):(8-20); The silica sol is obtained from a silicon source, an alcohol solvent and water in a molar ratio of 1:(2-12):(1-10) under the action of an acidic catalyst.

7. The preparation method according to claim 1, characterized in that: In step S1), the alumina sol is obtained from an aluminum source, an alcohol solvent and water; the silica sol is obtained from a silicon source, an alcohol solvent, water and an acidic catalyst; the aluminum source is selected from one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, aluminum isopropoxide or aluminum sec-butoxide; the silicon source is selected from one or more of methyl orthosilicate, ethyl orthosilicate, silica sol or water glass; the alcohol solvent is selected from one or more of methanol, anhydrous ethanol, isopropanol and n-butanol; the acidic catalyst is selected from one of hydrochloric acid, nitric acid and acetic acid; In step S1), the additive further comprises a drying control agent, and the drying control agent is selected from one or more of formamide or N,N-dimethylformamide; In step S3), the hydrophobic modifier is one or more of methyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, trimethylchlorosilane, phenyltriethoxysilane, dimethyldichlorosilane, trimethylethoxysilane, trimethylbromosilane, trimethoxysilane, tetramethylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, hexamethyldisiloxane, bis(trimethylsilyl)acetamide, and hexamethyldisilazane.

8. Alumina-silica aerogel obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the alumina-silica aerogel obtained by the preparation method according to any one of claims 1 to 7 in the fields of high-temperature thermal insulation, thermal insulation coatings, catalyst carriers or adsorption.

Citation Information

Patent Citations

  • Ordinary pressure preparation method for aluminium oxide composite aerogel rapped by silicon dioxide

    CN109621849A

  • Preparation method of Al2O3-SiO2 composite aerogel material by ambient drying

    CN110038493A

  • Macroporous low-density blocky composite gel and production process thereof

    CN113663610A

  • Method for preparing high-temperature-resistant SiO2-AxOy aerogel from metal inorganic salt

    CN114790004A